Delirium on Admission: Patterns in a Medicine Unit of a Tertiary Care Hospital in Bangladesh - Proma, Sanghita Banik; Saha, Arup Kumar; Saha, Dipannita; Sultana, Tania; Arifuzzaman, Md; Rahman, Aminur; Rahman, Abu Hayat Mohammod Waliur; Siddique, Abu Bakar; Amiruzzaman (Bangladesh Journal of Medicine, 2024)
Background: Delirium, a complex neuropsychiatric syndrome, poses challenges in clinical settings due to its varied aetiology and under diagnosis. This study aimed to explore the prevalence, demographic characteristics, and contributing factors of delirium as a presenting feature in the population admitted to a tertiary care hospital in Bangladesh. Limited studies on delirium in low- and middle-income countries necessitate a comprehensive investigation to inform healthcare practices in diverse settings. Methods: A prospective observational study was conducted on 102 patients diagnosed with delirium among a total of 2599 patients admitted to the medicine unit over six months. Delirium was assessed using the Confusion Assessment Method (CAM) score, with demographic variables and comorbidities analyzed. Results: The study identified a delirium prevalence of 3.8%, with stroke and poisoning as major contributors. Females (56.8%), individuals above 50 years (69.8%), and those with comorbidities (67.6%) exhibited higher susceptibility to delirium. The multifactorial aetiology included stroke (49.3%), poisoning (1.42%), electrolyte imbalance (0.76%), and others. Sedative poisoning predominated (45.9%) among poisoning cases. Conclusion: This study highlights the demographic and etiological dimensions of delirium. The significant impact of stroke, the underexplored realm of poisoning-related delirium, and the influence of age and comorbidities underscore the need for targeted interventions and increased awareness. Bangladesh J Medicine 2024; 35(1): 20-25